2021
DOI: 10.3390/su13147675
|View full text |Cite
|
Sign up to set email alerts
|

Building on Strategic eLearning Initiatives of Hybrid Graduate Education a Case Study Approach: MHEI-ME Erasmus+ Project

Abstract: Online courses are gaining popularity because they provide extensive and varied course material, information, knowledge, and skills, whilst also creating an effective educational online community. This research adopts a case study approach to focus on the teaching method and the manner in which a strategic commitment to eLearning provides scope for the development and implementation of top quality educational online fully accredited programs. Entrepreneurship focuses on developing businesses that add value and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Furthermore, research conducted by Madle ňák et al proved that well-planned flipped learning along with proper learning material provision can ensure an increase in learners' motivation, knowledge acquisition, confidence, and satisfaction. In so doing, the paper insisted that instructor-students communication and multiple approaches for checking content acquisition are important [32]. Research conducted by Şenda ǧ and Ferhan Odabaşi concluded that students' critical thinking skills can be increased more so through online PBL than an instructor-led online course [15].…”
Section: Effectiveness Of Online Educationsmentioning
confidence: 99%
“…Furthermore, research conducted by Madle ňák et al proved that well-planned flipped learning along with proper learning material provision can ensure an increase in learners' motivation, knowledge acquisition, confidence, and satisfaction. In so doing, the paper insisted that instructor-students communication and multiple approaches for checking content acquisition are important [32]. Research conducted by Şenda ǧ and Ferhan Odabaşi concluded that students' critical thinking skills can be increased more so through online PBL than an instructor-led online course [15].…”
Section: Effectiveness Of Online Educationsmentioning
confidence: 99%
“…Information technology is one of the fastestgrowing high-tech technologies and has become an important engine for my country's economic growth [8]. The role played by various related fields of information technology in the development of strategic emerging industries will directly affect the development process of my country's strategic emerging industries [9]. To cope with this situation, multisource information fusion emerges as a new frontier subject and research field [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to Réthy (2003), an individual's learning motivation is best guaranteed by the educational process that provides self-regulation. Madleňák et al (2021) propose the flipped classroom method. Another study examined in Hungary how the COVID-19 epidemic and the resulting social changes, influenced the education of theoretical economics (Fenyvesi et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%